2022
DOI: 10.3389/fphar.2022.964829
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanolamine-binding protein 4 deficiency exacerbates carbon tetrachloride-induced liver fibrosis by regulating the NF-κB signaling pathway

Abstract: Liver fibrosis is a pathological process which can progress to hepatocirrhosis, even hepatocellular carcinoma. Phosphatidylethanolamine-binding protein 4 (PEBP4) is a secreted protein involved in regulating many molecular pathways, whereas its roles in diseases including hepatic fibrosis remain undefined. The nuclear factor-κappa B (NF-κB) signaling pathway has been found to be involved in the development of liver fibrosis. In this study, we generated a hepatocyte-conditional knockout (CKO) mouse model of PEBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…This indicated that ASDURF may be a regulator of TGF-β1/Smad3 and NF-κB signaling pathways, and TGF-β1/Smad3 and NF-κB are important pathways in hepatic fibrosis. [3][4][5] This further supports the hypothesis that ASDURF is involved in managing hepatic fibrosis. The dual-luciferase test revealed that ASDURF enhanced ASNSD1 promoter activity, and Co-IP demonstrated that ASDURF could attach to ASNSD1 (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This indicated that ASDURF may be a regulator of TGF-β1/Smad3 and NF-κB signaling pathways, and TGF-β1/Smad3 and NF-κB are important pathways in hepatic fibrosis. [3][4][5] This further supports the hypothesis that ASDURF is involved in managing hepatic fibrosis. The dual-luciferase test revealed that ASDURF enhanced ASNSD1 promoter activity, and Co-IP demonstrated that ASDURF could attach to ASNSD1 (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…P‐smad3 and p‐p65 were downregulated after ASDURF interference in LX‐2 cell lines. This indicated that ASDURF may be a regulator of TGF‐β1/Smad3 and NF‐κB signaling pathways, and TGF‐β1/Smad3 and NF‐κB are important pathways in hepatic fibrosis 3–5 . This further supports the hypothesis that ASDURF is involved in managing hepatic fibrosis.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…PEBP4 has been reported to have anti-apoptotic function and is associated with the occurrence and development of various tumors [ 10 ]. In addition, PEBP4 is closely related to acute liver injury and liver fibrosis on account of its anti-inflammatory and liver-protective effects [ 11 , 12 ]. PEBP4 has been also identified as a new-found marker of type II AECs [ 13 ], whose dysfunction is involved in the occurrence and progression of ALI.…”
Section: Introductionmentioning
confidence: 99%